KEEFEKTIFAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN BERDIFERENSIASI TERHADAP KEAKTIFAN SISWA KELAS V DI SD ISLAM AL MADINA SEMARANG - Yuni Rahmawati; Joko Siswanto; Khoiruliono Abdullah; Arfilia Wijayanti (STKIP Subang, 2024)
The Problem Based Learning learning model is one way that teachers can apply to influence student activity. In implementing the problem based learning model there is a differentiated approach so that it is hoped that each child can receive instruction according to their abilities. The aim of this research is to determine the effectiveness of the Problem Based Learning model with a differentiated approach on the activity of class V students at Al Madina Islamic Elementary School Semarang. This research was conducted with 26 fifth grade students at Al Madina Islamic Elementary School Semarang. The method used is quantitative using paired T and N-gain assessments. In the paired T value, the significance value (2-tailed) is 0.000 <0.05, indicating that there is a difference between the pretest and posttest. Meanwhile, for N-gain, it is known that the mean is 0.6455. If this value is known using the gain test interpretation, it can be seen that 0.30 ≤ g ≤ 0.7 is included in the medium category.